Adsorptive Removal of Copper by Using Surfactant Modified Laterite Soil - Tien Duc Pham; Hoang Hiep Nguyen; Ngoc Viet Nguyen; Thanh Tu Vu; Thi Ngoc Mai Pham; Thi Hai Yen Doan; Manh Ha Nguyen; Thi Mai Viet Ngo (Journal of Chemistry)
Removal of copper ion (Cu2+) by using surfactant modified laterite (SML) was investigated in the present study. Characterizations of laterite were examined by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), inductively coupled plasma mass spectrometry (ICP-MS), and total carbon analysis. The optimum conditions for removal of Cu2+ by adsorption using SML were systematically studied and found as pH 6, contact time 90 min, adsorbent dosage 5 mg/mL, and ionic strength 10 mM NaCl. The equilibrium concentration of copper ions was measured by flame atomic absorption spectrometry (F-AAS). Surface modification of laterite by anionic surfactant sodium dodecyl sulfate (SDS) induced a significant increase of the removal efficiency of Cu2+. The surface modifications of laterite by preadsorption of SDS and sequential adsorption of Cu2+ were also evaluated by XRD and FT-IR. The adsorption of Cu2+ onto SML increases with increasing NaCl concentration from 1 to 10 mM, but at high salt concentration this trend is reversed because desorption of SDS from laterite surface was enhanced by increasing salt concentration. Experimental results of Cu2+/SML adsorption isotherms at different ionic strengths can be represented well by a two-step adsorption model. Based on adsorption isotherms, surface charge effects, and surface modification, we suggest that the adsorption mechanism of Cu2+ onto SML was induced by electrostatic attraction between Cu2+ and the negatively charged SML surface and nonelectrostatic interactions between Cu2+ and organic substances in the laterite.